The Effect of Reproductive Health Education on Adolescent Behavior in Sexually Transmitted Infections at SMA Negeri 1 Bandar Aceh Province - Handoko, Fithra Bagaskara; Nuraini, Nuraini; Nasution, Ramadhani Syafitri (Universitas Ibn Khaldun Bogor, 2025)
Sexually transmitted infections are still a serious problem in public health due to their impact on morbidity and mortality. Indonesia, as a developing country, also faces challenges in adolescent reproductive health, especially with the high prevalence of STIs among adolescents and young adults. The spread of this disease is still high due to a lack of knowledge and education in the field of reproductive health, as well as the influence of the environment and friends. Reproductive health education is one of the strategies that can be used to reduce risk and can help adolescents improve their knowledge and good attitudes in dealing with PIMS. The purpose of this study is to analyze whether there is an educational effect of reproductive health on adolescent behavior in sexually transmitted diseases at SMA Negeri 1 Bandar. The research design uses a quasi-experimental model with a pretest-posttest control group design. The data was analyzed using the non-parametric statistical test Wilcoxon Signed Rank Test to compare the differences. The location is at SMA Negeri 1 Bandar with a sample of all female students totaling 70 people. The results of the study showed that there were significant differences before and after education. Where in the group that was educated, a significance value (p) of 0.000 was obtained less than ɑ 0.05, so that Ho was accepted